Different patterns of intestinal transit time and anorectal motility in painful and painless chronic constipation. Issue 12 (December 1984) - Lanfranchi, G A; Bazzocchi, G; Brignola, C; Campieri, M; Labò, G
Abstract : Anorectal motility and gastrointestinal transit time were studied in 25 patients complaining of non-organic constipation. Colonic pain was reported by 14 patients, it was absent in the remaining 11. The group with painful constipation was composed of four men and 10 women and age onset of the symptom was 22.1 +/- 5.1 years. The other group was composed only of women and painless constipation was reported to have begun at 7.9 +/- 2.2 years previously. In the group presenting painful constipation higher values of the anal maximum resting pressure, of the amplitude of the rectoanal inhibitory reflex, lower values of sensation threshold, need to evacuate, maximum tolerable volume were recorded, in comparison with those registered in the painless constipation group. All these differences were significant. In the latter group the total transit time was always very slow (186.0 +/- 4.7 h), while it was quite variable in the other group, so that the mean was in the normal range (79.0 +/- 10.0 h). The data show that two different patterns of motor abnormalities can be recognised in constipated patients. The presence of colonic pain can suggest the characteristics of the underlying motor abnormality.